The Influence of Human Resources, Communications Information Technology (ICT), and Leadership on The Quality of Passport Issuance Public Services in Manokwari Class I Non-TPI Immigration Offices - Nurliana, Dian Pratiwi Agustina; Hafel, Muhlis; Herningsih, Herningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Based on the results of research, analysis, and discussion of case studies at the Class I Non-TPI Manokwari Immigration Office, it is concluded that the influence of Human Resources, Information Communication Technology, and Leadership on the Quality of Passport Issuance Services at the Office is very significant. Human Resources have a big impact on service quality, as evidenced by the high significance value (t = 4.991, p < 0.05) and the indicator "Timely completion of work" which gets the highest score. Likewise, the use of Information Communication Technology (t = 4.955, p < 0.05) and the role of Leadership (t = 2.623, p < 0.05) also have a strong influence on service quality. Apart from that, the results of the analysis show that the three of them together contribute significantly to the Quality of Passport Issuance Services (F count = 81.542, F table = 2.79). Thus, the role and optimal use of Human Resources, Information Communication Technology, and Leadership is very important to improve the quality of services at the Class I Non-TPI Manokwari Immigration Office.